Utilization of modified copper slag activated by Na2SO4 and CaO for unclassified lead/zinc mine tailings based cemented paste backfill. (15th July 2021) - Chen, Qiusong; Tao, Yunbo; Feng, Yan; Zhang, Qinli; Liu, Yikai
Abstract: Serious heavy metals pollution was characterized in the lead/zinc mine tailings dam and surrounding soils, as well as copper slag disposal sites. This study investigates the efficacy of modified granulated copper slag (MGCS) as a partial replacement of ordinary Portland cement (OPC) for lead/zinc mine tailings-based cemented paste backfill (CPB) application using Na2 SO4 (CSN) and CaO (CSC) as alkali-activated materials. The effect of different scenarios was ascertained by unconfined compressive strength (UCS). Also, the correlated microstructural evolution and mineralogical phase generation were obtained by scanning electron microscopy (SEM), mercury intrusion porosimetry (MIP), and X-ray diffraction (XRD). The main findings proved that CSN was more effective in improving mechanical performance. Na2 SO4 was found associated with C–S–H gel formation accompanied by a compact microstructure and better pore distribution with lower porosity. However, deposition of chloride compound was found in the surface layer of CSN samples, which could bring deterioration to the mechanical properties. Results above extend the knowledge of reusing MGCS as supplementary material to CPB, promoting the concept of a circular economy demand for both lead/zinc mine extraction and copper industries. Graphical abstract: Image 1 Highlights: Na2 SO4 contributes to higher mechanical properties. Porosity decreases with Na2 SO4 . Too much Na2 SO4 can bring precipitation.